Claiming the hydraulic network of Angkor with Viṣṇu: A multidisciplinary approach including the analysis of archaeological remains, digital modelling and radiocarbon dating: With evidence for a 12th century renovation of the West Mebon. (October 2016) - Feneley, Marnie; Penny, Dan; Fletcher, Roland
Abstract: Prior to the investigations in 2004–2005 of the West Mebon and subsequent analysis of archaeological material in 2015 it was presumed that the Mebon was built in the mid-11th century and consecrated only once. New data indicates a possible re-use of the water shrine and a refurbishment and reconsecration in the early 12th century, at which time a large sculpture of Viṣṇu was installed. Understanding the context of the West Mebon is vital to understanding the complex hydraulic network of Angkor, which plays a crucial role in the history of the Empire. Graphical abstract: Highlights: Digital reconstruction of the West Mebon including animated flyover. New insights indicating the West Mebon was important within network of the hydraulic system at Angkor. 14C dating, iconographic analysis and archaeology show the shrine was consecrated to be first Śaivite then Vaiṣṇavite; the second consecration being in the early 12th C. This is the first publication and analysis of important primary resources and artefacts found at the Mebon which indicate a later date for the installation of the massive bronze sculpture of Viṣṇu found there.